Achieving impact in research - Denicolo, Pam (Los Angeles, California : Sage, 2014)
This unique addition to the Success in Research series addresses the importance of understanding and achieving impact for the purposes of gaining research funding and reporting achieved impact for the Research Excellence Framework (REF). The book includes contributions from researchers and researcher developers who feel that impact is ill-defined and poorly understood despite its prevalence in policy documents, websites and institutional activities. This succinct and cohesive text draws on the expert contributors' collective research practice, knowledge and experience.
1. What is the meaning of impact in relation to research and why does it matter? A view from inside academia -- 2. What is the meaning of the Impact Agenda - is it a repackaged or a new entity? Views from inside the Research Councils -- 3. How does the Impact Agenda fit with attitudes and ethics that motivate research? -- 4. What are the different characteristics of research impact? -- 5. When might research impact be apparent? -- 6. How can impact be planned into research proposals? -- 7. How can impact evaluation be planned? -- 8. How can impact be evidenced: practical methods? -- 9. What skills are needed to be an impactful researcher? -- 10. How can knowledge exchange support the development of impact through partnerships and university infrastructures? -- 11. How can you become an impactful researcher?
Includes index.
Keywords: SOCIAL SCIENCES -- RESEARCH -- METHODOLOGY